(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Implementing moderation in Islamic education in schools is an important step to encourage critical thinking, tolerance, and the integration of moderate religious values ​​in the curriculum. This research aims to find out how religious moderation is implemented in Islamic education in schools. Which consists of a discussion regarding the objectives of implementing religious moderation, implementing religious moderation in Islamic education in schools, the role of teachers in implementing religious moderation, and evaluating and monitoring the implementation of religious moderation. This research uses qualitative research methods by collecting library research data, the data analysis is carried out using qualitative descriptive methods to explain the facts about the implementation of religious moderation in Islamic education in schools. The results of this research are that the implementation of moderation in education in schools can also to foster religious moderation through school programs and activities. Then implementing moderation in education at school can also foster religious moderation through school programs and activities